Adherence of cooperatives to the compliance system considering the current legislation (Desenvolvimento em Questão, 2024)
This study aimed to analyze the adherence of cooperatives in the Metropolitan Region of Belém (RMB) to cooperative laws and norms, based on the fifth principle of cooperativism: Education, Training and Information. Given this, a theoretical basis was sought on the relationship between human capital, the cooperative principle and compliance, combining this knowledge with the legal basis that supports cooperativism. In this sense, forms were applied to 32 cooperatives. In the data analysis, document and content analysis was conducted, with two categories of analysis being developed: i) corporate aspects; ii) accounting-tax aspects. The results showed that the adherence of cooperatives to current standards is moderately with positive and negative points. Positively, the concern with transparency stands out, evidenced by accountability as an item on the agenda of all cooperatives. Negatively, it was found, in an expressive number, that the shares, in the event of the death of the cooperative member, are transferred to a family member, who becomes a partner, contrary to Law 5.764/71 and the Civil Code itself. Finally, it is hoped that this contribution to the literature will introduce new discussions and draw the attention of cooperatives to the importance of complying with current regulations that regulate their procedures. This can help avoid fines and errors in operational procedures, which can result in the loss of tax and tax benefits. Furthermore, the need for continuous investment in education and information by cooperatives stands out, to qualify and train their employees, aiming to mitigate conflicts of interest.
Keywords: cooperative education; compliance; Law nº 5.764/71